An Automatic Voice Test Method of HMI for Train with PerceptualEvaluation of Speech Quality - GAO Feng; ZHANG Hongwei (Kongzhi Yu Xinxi Jishu)
During the train HMI speaker test, operator should judge the quality of voice by ear, which causes difference in HMI voice quality test by the influence of environment nosie, HMI assembly, etc. It describes a automatic detection method which uses microphone to sample the voice of HMI, and a PESQ algorithm is used to automatically detect and evaluate the voice from HMI. Simulation results show that the PESQ score is consistent with the artificial subjective score, and the maximum deviation is 0.14, which shows that the proposed method realizes the automatic evaluation of perceptual speech quality and ensures the consistency of test.